2014
DOI: 10.13189/ujme.2014.020605
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Surface Roughness in EDM for D2 Steel by RSM-GA Approach

Abstract: Modeling and optimization of machining parameters are very important in any machining processes. The current study provides predictive models for the functional relationship between various factors and responses of electrical discharge machined AISI D2 steel component. Surface Roughness (Ra) is important as it influences the quality and performance of the products, hence the minimization of surface roughness in manufacturing sectors is of maximum importance. It is also realistic and desirable if the finished p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In their study, Anitha et al reported the results obtained by processing AISI D2 die steel on an EDM machine with processing parameters determined as discharge current, pulse time, waiting time, and voltage, with three different values for each factor. As a result of the study, in order to find the most suitable conditions for the regression model developed with response surface methodology (RSM) for minimum surface roughness, the results were analyzed again with genetic algorithm (GA) and the formula to minimize the processing time was determined [18]. In his study, Ali investigated the machining of AISI D2 cold work tool steel on an EDM machine with different processing parameters (amperage and time-on) using a copper electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Anitha et al reported the results obtained by processing AISI D2 die steel on an EDM machine with processing parameters determined as discharge current, pulse time, waiting time, and voltage, with three different values for each factor. As a result of the study, in order to find the most suitable conditions for the regression model developed with response surface methodology (RSM) for minimum surface roughness, the results were analyzed again with genetic algorithm (GA) and the formula to minimize the processing time was determined [18]. In his study, Ali investigated the machining of AISI D2 cold work tool steel on an EDM machine with different processing parameters (amperage and time-on) using a copper electrode.…”
Section: Introductionmentioning
confidence: 99%
“…It is a sophisticated mathematical and computer science method that establishes a mathematical relationship between a response variable (π‘Œ) and one or more independent variables (𝑋 𝑖 , where 𝑖 can be 1, 2, ..., 𝑛). In recent years, researchers in various fields, such as prediction of friction stir welding [40], hard turning [41], turning process [42], machine condition monitoring [43], drilling process [44], electrical discharge machining process [45], extensively use ANN modeling, which underlines the importance of this mathematical technique in material removal machining. ANNs consist of three interconnected layers: the input layer, the hidden layer, and the output layer (see figure2) [46].…”
Section: Ann-based Modelingmentioning
confidence: 99%
“…Quadratic vs 2FI model is the recommended model because it has a p-value of 0.0002. The p value < 0.05 which means it is real [21]. The p value <0.05 means that the probability of error in the model is less than 5% or the quadratic model has a significant effect on the response.…”
Section: Sequential Model Of Sum Of Squares Model Selectionmentioning
confidence: 99%